Preoperative identification of bleeding site caused by angiodysplasia of the small bowel by means of selective arteriography and application of methylene blue - Stanojeviċ Goran; Bošnjaković Petar; Stojanoviċ Miroslav; Jovanoviċ Milan; Branković Branko; Radojković Milan; Katić Vuka V. (Vojnosanitetski Pregled)
Background. Small bowel hemorrhages are rare and account for 2-10% of all gastrointestinal bleedings. In case that surgery is necessary, identification of the bleeding site is the most important problem. Case report. We presented here the case of a 65-year old man, admitted for urgent care of massive lower gastrointestinal bleeding. After reanimation and normalization of vital parameters, selective arteriography was done. A contrast extravasation site was identified at the level of jejunal branches of a. mesenterica superior and labeled by means of methylene blue application. Immediately after we performed conservative resection of the labeled jejunal loop in 10 cm length and terminoterminal anastomosis. The preparation was sent for histopathologic examination - small bowel angiodysplasia was identified. The patient was monitored in three month intervals in the next two years and new bleeding events were not observed. Conclusion. Bleeding caused by small bowel angiodysplasia is a significant diagnostic problem in cases in whom urgent surgery is required. Combined preoperative selective arteriography and methylene blue application make possible precise identification of the bleeding site as well as conservative small bowel surgery, avoiding thus the risk and danger of malabsorption syndrome.